Over a million students use our free study notes to help them with their homework
x(x+1) - x(x-1)/(x-1)(x+1)x2+x-x2+x/(x-1)(x+1)2x/x2+x-x-12x/(x2-1)
13y - 5 = 9y + 27 First we must collect all similar terms together on either side of the equation: 13y - 9y = 27 + 5. As you can see, if a term is moved to the other side of the equation, the opposite sig...
(x+2)(x-1)=0 x+2=0x= -2x-1=0x=1
Firstly, demonstrate with an example: Solve: 3x + y = -9 and x2 + 2x - 3 = yRearrange the first equation to get "y" by itself by moving parts of the equation to the other side e.g. y ...
Pythagoras theorem can be used to calculate the length x of the triangle. The length of the hypotenuse is equal to the square root of a2 + b2. When given length a and b, you are able...
←
468
469
470
471
472
→
Internet Safety
Payment Security
Cyber
Essentials